2000
DOI: 10.1590/s0100-83582000000200014
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de herbicidas, aplicados em pós-emergência, às plantas de alfafa

Abstract: Foram conduzidos doi experimentos na UNESP/Jaboticabal, em casa-de-vegetação, com o objetivo de avaliar-se a toxicidade de diferentes herbicidas, aplicados em pós-emergênica, às plantas de alfafa. No primeiro, utilizou-se de um delineamento experimental com parcelas inteiramente casualizadas para avaliar-se os efeitos fitotóxicos dos seguintes herbicidas: MSMA, clethodim + óleo mineral, lactofen, fluazifop-pbutil, fomesafen + óleo mineral haloxyfop-methyl + óleo mineral, fenoxaprop-ethyl, chlorimuronethyl, hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
(1 reference statement)
3
5
0
2
Order By: Relevance
“…A similar result was found by Silva et al (2004). However, the phytotoxicity symptom found by Mello et al (2000) was considered as average, with decreased dry mass and lower plant development. Mesbah et al (2005) found injuries to alfalfa due to phytotoxicity caused by the herbicides imazethapyr and imazamox after application to plants 15 cm tall.…”
Section: Evaluation Of the Selectivity Of Herbicides Applied To Alfalsupporting
confidence: 83%
See 4 more Smart Citations
“…A similar result was found by Silva et al (2004). However, the phytotoxicity symptom found by Mello et al (2000) was considered as average, with decreased dry mass and lower plant development. Mesbah et al (2005) found injuries to alfalfa due to phytotoxicity caused by the herbicides imazethapyr and imazamox after application to plants 15 cm tall.…”
Section: Evaluation Of the Selectivity Of Herbicides Applied To Alfalsupporting
confidence: 83%
“…Silva et al (2004) showed that alfalfa treated with chlorimuron-ethyl showed initial symptoms of phytotoxicity with full recovery after 14 DAA. Mello et al (2000) obtained the same result, with less negative effects on alfalfa between the first and second cuts.…”
Section: Evaluation Of the Selectivity Of Herbicides Applied To Alfalsupporting
confidence: 61%
See 3 more Smart Citations